2017
DOI: 10.35808/ersj/822
|View full text |Cite
|
Sign up to set email alerts
|

Revitalization Model for Village Unit Cooperative in Indonesia

Abstract: Rapid expansion by modern businesses impacts significantly on traditional businesses, including Village Unit Cooperative as a business model mandated by The Indonesian Primary Constitution, i.e, The Constitution of 1945. Several weaknesses faced by Village Unit Cooperative against modern business include limited resources (i.e, financial and infrastructure), low level of education for employees and managers, traditional managerial style, and so-forth. Data collected through in-depth interview with the head of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…As explained by Ropke (1995) cooperatives are business organizations whose owners or members are also the company's main customers. Moreover, the VUC is an all-round cooperative which commonly consists of villagers where its working area usually covers one district (Riswan et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As explained by Ropke (1995) cooperatives are business organizations whose owners or members are also the company's main customers. Moreover, the VUC is an all-round cooperative which commonly consists of villagers where its working area usually covers one district (Riswan et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Village Unit Cooperative (hereafter, VUC) is a type of business that oversees various business fields, such as agricultural production facilities, trade, agriculture, savings and loans, and so-on. This type of business has been going on for a long time in Indonesia and its benefits have been felt by the wider community and contributed to providing employment and driving the economy of the country (Riswan et al, 2017). In addition, cooperative is a type of business entity mandated by the basis of the constitution for the Indonesian State, i.e., the 1945 Constitution.…”
Section: Introductionmentioning
confidence: 99%
“…The government notably guaranteed both marketing and market price to encourage the growth of farm cooperatives. A research from Riswan, Suyono and Mafudi (2017), found that during the New Order or the Suharto regime from 1980 to 1990, Vucs experienced success, notably in financial performance. However, the success in that period was mainly caused by the monopolistic system in the Vucs in managing seeds and fertilizers.…”
Section: The Cooperative Structure In Indonesiamentioning
confidence: 99%
“…Unfortunately, the rapid growth of the quantity of cooperatives in Indonesia is not matched by the increasing participation of members. Participation of members in Indonesian cooperatives is still low (Riswan et al, 2017) and their awareness to participate both professionally and actively is still below the expectations of the government. Taiwo (2011Taiwo ( , 2015; Ernita, et al, (2014ab, 2015Ernita, et al, (2014ab, , 2016; and Hadayati et al (2016), show that member participation is vital in improving cooperative performance.…”
Section: Introductionmentioning
confidence: 99%